Simple Colorimetric DNA Biosensor Based on Gold Nanoparticles for Pork Adulteration Detection in Processed Meats - Bambang Kuswandi; Agus A Gani; Nia Kristiningrum; Musa Bin Ahmad (International Frequency Sensor Association (IFSA), 2024)
Non-Indexed Publication